Optimization and validation of online column-switching assisted HPLC-spectrometric method for quantification of dansylated endocannabinoids and neurotransmitters in animal models of brain diseases - Maria Baranyi; Beata Sperlagh (Open Journal of Analytical and Bioanalytical Chemistry - Peertechz Publications, 2019)
In scientific research, animal modelling of human disease is pivotal in both studying the mechanisms of the disease and developing potential therapies. An imbalance in the interaction between the endocannabinoid (eCB) and Neurotransmitter (NT) systems may play a role in the pathogenesis of neurological diseases, such as Parkinson's Disease (PD). The major limitation of current neurochemical practice is that different assays are used to measure each class of NTs. We present a liquid chromatography-spectrometric method that utilizes 5-dimethylamino naphthalane-1-sulfonyl (dansyl) chloride derivatizing reagent for the simultaneous measurement of nine different types of neurotransmitters. In order for our method to achieve the highest possible sensitivity, we tested the following reaction parameters: reaction medium and pH; the effect of reagent concentration; reaction temperature and time, both of which influence the efficiency of dansyl derivative formation of eCBs; and Amino Acids (AAs) and Monoamines (MAs) that are present in the sample together. To achieve the required analytical sensitivity, online solid phase extraction techniques were used to purify and enrich the dansylated sample. The optimal sample enrichment and clean-up time were calculated from the breakthrough volume of dansyl hydroxide, taken on a capture column (ACE Ultra Core Super C-18), when the mobile phase contained 1.9%(v/v) of acetonitrile and 1.1%(v/v) of methanol in formic acid ammonium salt buffer at a flow rate of 0.3 ml/min. The linear range of calibration was between 50-1575 pmol/ml for all the analytes (aspartic acid, glutamic acid, glycine, γ-aminobutyric acid, dopamine, norepinephrine, serotonin, N-arachidonylethanolamide, or anandamide, and 2-arachidonylglycerol). The Limit of Detection (LOD) and Quantification (LOQ) ranged between 15.75-118.5 pmol and 26.5-196.5 pmol respectively. The precision (repeatability) was in the range of 5.7%-9.9% for each analyte. This method was applied to investigate neurochemical changes in a mouse model of Parkinson's disease in the presence and absence of P2x7 and P2Y12 purinergic receptors. In conclusion, the present method shows acceptable precision and adequate sensitivity in quantifying the basal levels of the endocannabinoids, and it is well suited for the simultaneous determination of neurotransmitters and endocannabinoids.